Effect of using phase change materials on thermal performance of passive solar greenhouses in cold climates - M.M. Ismail; I. Dincer; Y. Bicer; M.Z. Saghir (International Journal of Thermofluids, 2023)
Passive solar greenhouses are crucial for sustainable agriculture in cold regions, but they face challenges in temperature regulation, especially at night when temperatures drop down significantly. Phase Change Materials (PCMs) appears to be a potential solution to improve the thermal stability by storing and releasing large amounts of thermal energy during phase changes. In the present study, it is obtained that incorporating PCMs into the north wall of a passive solar greenhouse helps extend the growing season by up to 48 days, increase the average temperature during the growing season from 12.1 °C to 24.8 °C, and enable a wider range of crops to be cultivated. This study provides valuable insights into the feasibility of using PCMs in passive solar greenhouses to improve temperature regulation and energy efficiency in cold climates.